Cathode-focused high-current arc: Heat source development with stable keyhole in stationary welding. (November 2019) - Chen, S.Y.; Liu, Z.M.; Zhao, X.C.; Lv, Z.Y.; Fan, X.G.
Highlights: A three-dimensional numerical model was established for the high-current free burning arc keyhole welding. A novel suitable combined heat source model was proposed based on the arcing principle. The evolution behavior of arc source, temperature field and flow field is visualized to exhibit how the high-current free burning arc creates a stable keyhole. Abstract: A three-dimensional numerical model was established to investigate the thermal coupling mechanism in the K-TIG (Keyhole Tungsten Inert Gas) keyhole and weld pool. Especially, to reflect the energy distribution in the new-developed high-current free burning arc, a novel, suitable combined heat source model was proposed. The dynamic process of heat source and the corresponding temperature field were studied to reflect the effect of arc on the workpiece. Keyhole evolution with temperature distribution and fluid flow in the weld pool was investigated to further explore the keyhole influence on the heat transfer and mechanical energy of the weld pool. Some new features of K-TIG were discovered. The higher temperature molten metal is distributed mainly in the upper part instead of the bottom of the weld pool, and the weld pool volume of K-TIG is large, up to 50 mm 3 . Finally, the first emerging time of a fully penetrated keyhole, keyhole size, and fusion line size were measured in stationary welding experiments. The simulation results agreed well with the measured data. The results lay a foundation for understanding the coupling behavior in energy source-keyhole-weld pool system, and they could promote the engineering application of K-TIG process.